2017
DOI: 10.1038/nmat4957
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured organic semiconductor films for molecular detection with surface-enhanced Raman spectroscopy

Abstract: π-Conjugated organic semiconductors have been explored in several optoelectronic devices, yet their use in molecular detection as surface-enhanced Raman spectroscopy (SERS)-active platforms is unknown. Herein, we demonstrate that SERS-active, superhydrophobic and ivy-like nanostructured films of a molecular semiconductor, α,ω-diperfluorohexylquaterthiophene (DFH-4T), can be easily fabricated by vapour deposition. DFH-4T films without any additional plasmonic layer exhibit unprecedented Raman signal enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
216
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(223 citation statements)
references
References 57 publications
6
216
1
Order By: Relevance
“…Currently, the enhancement factor obtained using bare organic semiconductor thin films is 10 3 and an enhancement factor of 10 10 with the addition of a plasmonic (gold) layer 4 . The use of thin film organic semiconductor material relies solely on charge transfer and molecular aggregation mechanism for SERS enhancement.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the enhancement factor obtained using bare organic semiconductor thin films is 10 3 and an enhancement factor of 10 10 with the addition of a plasmonic (gold) layer 4 . The use of thin film organic semiconductor material relies solely on charge transfer and molecular aggregation mechanism for SERS enhancement.…”
Section: Articlementioning
confidence: 99%
“…SERS with organic semiconductors presents distinctive advantages, including structural adaptability, tunable charge mobility, low effective carrier mass 2 . Recently reported organic semiconductor sensors are thin films 3,4 . However, organic semiconductors rely primarily on charge transfer mechanism for SERS enhancement which hinders the sensitivity to a great extent.…”
mentioning
confidence: 99%
“…Furthermore, by combining the strong EM enhancement of noble metals with the high selectivity and spectral stability of semiconductors in the fabrication of semiconductor–metal hybrid nanostructures, promising SERS platforms for the quantitative trace detection of target molecules could be obtained . One related study demonstrated that an EF up to 10 10 was accomplished by coating α‐ω‐diperfluorohexylquaterthiophene (DFH‐4T) films with a thin gold layer, as shown in Figure . Yilmaz et al.…”
Section: Applicationsmentioning
confidence: 99%
“…Among the different SERS‐active materials researched, organic semiconductors have recently attained increasing attention due to their exceptional properties, including tunable bandgap, high electron mobility, infinite Bohr radius . Current research on organic semiconductors for SERS application is limited to molecular sensing since most of these probes are 1D nanoprobe (thin films) fabricated through deposition. The large area of these organic semiconductor probe prevents them from being applied for cellular detection.…”
Section: Introductionmentioning
confidence: 99%